The perception and views of business support programmes among women micro entrepreneurs in the West Coast of Sabah - Merlyn Rita Buncha; Salmah Topimin; Haslinda Hassan; Siti Nor Bayaah Ahmad; Irma Wani Othman (Academic Inspired Network, 2022)
Women micro entrepreneurs’ awareness of business support programmes remains largely highlighted. This paper examines the perception and views of the women micro entrepreneurs in the West Coast of Sabah, Malaysia in late 2018. This study adopts an interpretative approach and uses semi-structured interviews as the main data collection technique in exploring the perceptions and views of five women micro entrepreneurs on business support programmes. All women entrepreneurs were identified using a list provided by an organisation that provides business support for women entrepreneurs in research setting. The selection process of interviewing women micro entrepreneurs, using a purposive sampling technique was based on the following criteria: 1) formally registered their businesses, 2) own micro and small businesses, and 3) run a full-time business. The findings reveal that majority of them were aware of the business support programmes provided by the government and were satisfied with the business support programmes as well as they have been received many guides and additional info from the government agencies. This study found that the business support programmes are beneficial for women micro entrepreneurs. Therefore, the Sabah state government as well as relevant institutional business support programmes should continuously promote various types of types of aids and assistance such as microcredit facilities, short-term loan, marketing and ICT tools and equipment to facilitate women microbusinesses. The future study is needed to emphasis on the important of fostering awareness of business support programmes among women micro entrepreneurs, thus, adding to the body of knowledge about empowering women's entrepreneurship.